2010
DOI: 10.3389/fnhum.2010.00224
|View full text |Cite
|
Sign up to set email alerts
|

The Intense World Theory – A Unifying Theory of the Neurobiology of Autism

Abstract: Autism covers a wide spectrum of disorders for which there are many views, hypotheses and theories. Here we propose a unifying theory of autism, the Intense World Theory. The proposed neuropathology is hyper-functioning of local neural microcircuits, best characterized by hyper-reactivity and hyper-plasticity. Such hyper-functional microcircuits are speculated to become autonomous and memory trapped leading to the core cognitive consequences of hyper-perception, hyper-attention, hyper-memory and hyper-emotiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
325
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 401 publications
(367 citation statements)
references
References 322 publications
38
325
1
3
Order By: Relevance
“…Ongoing neural activity can be assessed noninvasively during a resting-state EEG recording, i.e., in the absence of task performance or sensory stimulation, in which patterns of neural oscillations may be detected [2]. It has been suggested that elevated oscillatory activity in ASD might indicate hyperactivity in cortical circuits, and subsequently may be associated with the ''autistic'' state [3,4], which is in agreement with a recent review summarizing EEG abnormalities during resting-state paradigms in ASD, reporting increased power in low (delta, theta) and high frequencies (beta, gamma) and reduced activity in middlerange frequencies (alpha) [2]. A few experimental studies report altered resting-state gamma activity by EEG or MEG.…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing neural activity can be assessed noninvasively during a resting-state EEG recording, i.e., in the absence of task performance or sensory stimulation, in which patterns of neural oscillations may be detected [2]. It has been suggested that elevated oscillatory activity in ASD might indicate hyperactivity in cortical circuits, and subsequently may be associated with the ''autistic'' state [3,4], which is in agreement with a recent review summarizing EEG abnormalities during resting-state paradigms in ASD, reporting increased power in low (delta, theta) and high frequencies (beta, gamma) and reduced activity in middlerange frequencies (alpha) [2]. A few experimental studies report altered resting-state gamma activity by EEG or MEG.…”
Section: Introductionmentioning
confidence: 99%
“…These changes at the level of a single neuron or synapse lead to the development and maintenance of neural circuitry. We and others have suggested that abnormalities in regulation of these synaptic changes lead to larger-scale alterations in plasticity and metaplasticity that may account for the neurological and behavioral phenotype of ASD and fragile X syndrome (FXS) (Markram and Markram 2010;Oberman et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…ASD is diagnosed by clinical criteria, and the exact brain dysfunction that leads to the behavioral phenotype in nonsyndromic ASD remains unknown. However, altered mechanisms of synaptic, use-dependent plasticity and metaplasticity are likely essential components of the ASD pathophysiology (Dolen and Bear 2009;Markram and Markram 2010;Oberman et al 2010Oberman et al , 2012Oberman 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These include the "Intense World" hypothesis of Markram and Markram (2010), in which stimuli experienced as painfully intense lead to selective attention and avoidance of social input. Similarly, Kinsbourne (2011) suggests that an unstable arousal system leads to avoidance of unpredictable social input, to restricted interests, and to inward focus of attention.…”
Section: Implications For Theorymentioning
confidence: 99%